Normalisasi Trend Nikah Muda: Analisis Struktural Fungsional dan Maqashid Syariah - Adji Pratama Putra; Agung Burhanusyihab (Fakultas Syariah IAIN Madura, 2023)
This paper examines the tren of young marriage analysis of structural-functional theory and maqashid sharia. Marriages that are supposed to create happy and eternal families, cannot be performed because of young marriages that are not yet physically, mentally, and spiritually immature. Young married couples are caused by economic, social, and cultural factors, even accidents (due to getting pregnant out of wedlock). This is almost the case in various regions, including in the Depok district. Functional structural theory and sharia maqashid are used as cultural optimizers for young marriage trens. Researchers used empirical juridical methods and took primary data from a sample of men and women who intermarried aged 12-18. These findings tend to have a more negative impact, due to the absence of mental, emotional, and physical readiness to foster a family. Mediocre education and knowledge factors are also why young married couples find it challenging to find work which causes financial problems in the household.